Electrolyte solution, secondary battery, and electric device

By introducing phosphoryltriamine compounds into the electrolyte of lithium-ion batteries, the problem of H2O and PF6-reaction in the electrolyte is solved to generate HF, which inhibits the increase in acidity and the damage of the SEI film, improves the circulation and storage performance of the battery, and improves the safety of the battery.

CN119542540APending Publication Date: 2025-02-28ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411895885.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Trace amounts of H2O in the electrolyte of lithium-ion batteries react chemically with PF6- to generate HF, causing the acidity of the electrolyte to rise, destroy the SEI film, increase the DC internal resistance of the battery, and deteriorate the circulation performance and safety.

Method used

The additives including phosphoryltriamine compound are introduced into the electrolyte solution, and the free H+ in the electrolyte solution is suppressed by the lone pair electron complexing of the P and N atoms, and the acidity is increased, and oxidized and decomposed on the surface of the positive electrode to form a dense inorganic layer rich in N and P, reducing the impedance of SEI.

Benefits of technology

Effectively inhibit the continuous decomposition of the electrolyte, improve the high-temperature circulation of the battery and the gas production performance of the stored process, and improve the circulation performance and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542540A_ABST
    Figure CN119542540A_ABST
Patent Text Reader

Abstract

The embodiment of the invention provides an electrolyte, a secondary battery and a power utilization device, the electrolyte comprises a non-aqueous solvent, a lithium salt and an additive, the additive comprises a phosphoramidite compound, and the structural formula of the phosphoramidite compound is as shown in the following formula (I): # imgabs0 #, and R1-R6 are respectively one or more of alkyl, fluoroalkyl and alkylene with the C atom number of 1-3. In the embodiment, lone pair electrons in P and N atoms in molecules of the phosphoramidite compound have protonic property and can be complexed with free H < + > in an electrolyte, so that SEI damage caused by acidity increase of the electrolyte is avoided; meanwhile, the phosphoramidite compound can be oxidized and decomposed on the surface of the positive electrode to form a compact inorganic layer rich in N and P, so that the impedance of SEI is effectively reduced. The two action mechanisms of the phosphoramidite compound can inhibit the continuous decomposition of the electrolyte, improve the storage and cyclic gas production of the battery, and enhance the safety performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the field of batteries, and in particular, to electrolytes, secondary batteries and electrical devices. Background Art

[0002] In the development of batteries in the field of new energy, lithium-ion secondary batteries have the advantages of high energy density, long cycle life, high average output voltage, high safety performance, low self-discharge rate, adaptability to extreme environments, and green environmental protection. They are widely used in the fields of medical treatment, aerospace, artificial intelligence, electric vehicles, large-scale energy storage, etc. Commercial lithium-ion secondary battery electrolytes use carbonate as solvent and lithium hexafluorophosphate (LiPF6) with high solubility and dissociation as lithium salt, assisted by various functional additives to ensure that lithium-ion batteries can be applied to multiple scenarios.

[0003] However, LiPF6 is extremely sensitive to H2O (water). Trace amounts of H2O in the electrolyte react with PF6. - (hexafluorophosphate) reacts chemically to generate HF (hydrogen fluoride), which increases the acidity of the electrolyte. On the one hand, the generated HF will destroy the SEI film (solid electrolyte interface film) inside the battery, causing the lithium ions to undergo an irreversible chemical reaction on the negative electrode side, consuming active lithium ions; on the other hand, the destruction of SEI triggers a continuous reaction of the electrolyte on the negative electrode side, generating more gas, increasing the pressure inside the battery, causing battery bulging and leakage; the above two situations cause the battery's DCR (direct current internal resistance) to increase, thereby deteriorating the battery's high and low temperature cycle performance and storage performance, and reducing the battery's service life. Summary of the invention

[0004] The present invention introduces an additive including a phosphorothioic acid triamide compound into the electrolyte to eliminate free H in the electrolyte. + , inhibit the increase of electrolyte acidity, improve gas production during high-temperature cycling and storage, and enhance the battery's cycling performance and safety.

[0005] Some embodiments of the present application provide an electrolyte, including a non-aqueous solvent, a lithium salt and an additive, wherein the additive includes a phosphorothioate compound, and the phosphorothioate compound has a structural formula as shown in the following formula (I):

[0006]

[0007] Wherein, R1-R6 are each one or more of an alkyl group, a fluoroalkyl group, and an olefin group having 1 to 3 carbon atoms, and optionally, R1-R6 are independently selected from one or more of a methyl group, an ethyl group, a difluoromethyl group, and a vinyl group. In an embodiment, the lone pair of electrons in the P and N atoms in the above-mentioned phosphorothiamidite compound molecule is protophilic and can complex the free H in the electrolyte. +, avoiding the damage of SEI caused by the increase of electrolyte acidity; at the same time, the phosphoric acid triamide compound can also oxidize and decompose on the surface of the positive electrode to form a dense inorganic layer rich in N and P, effectively reducing the impedance of SEI. The two action mechanisms of the phosphoric acid triamide compound can inhibit the continuous decomposition of the electrolyte, improve battery storage and cycle gas production, and enhance the safety performance of the battery.

[0008] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the phosphorus amide compound is 0.1%-1.0%, and can be 0.5%. Specifically, when the amount of the phosphorus amide compound used is low, the free H in the electrolyte is + The complexing ability is insufficient, and more gas is produced in the later stage of the cycle, resulting in a sudden drop in the cycle; when the amount of the phosphorus triamide compound used is high, the BOL DCR of the battery is large, and lithium deposition of the negative electrode is likely to occur in the later stage of the cycle, affecting the cycle performance of the battery. Therefore, the amount of phosphorus triamide compound added to the electrolyte needs to be limited to a reasonable range. In some embodiments, based on the total mass of the electrolyte, the total mass of the additive accounts for ≥2%.

[0009] In some embodiments, the additives of the present application also include one or more of vinyl carbonate (VC), 1,3-propane sultone (PS), fluoroethylene carbonate (FEC), vinyl sulfate (DTD), methylene disulfonate (MMDS), tris(trimethylsilyl) phosphate (TMSP), and tetravinyl silane (TVSI) (which can be used as film-forming additives), and based on the total mass of the electrolyte, the mass proportion of the additives other than the phosphorus triamide compound in the above additives is 0.5%-5%. In some specific embodiments, based on the total mass of the electrolyte, the additives can include a phosphorus triamide compound combination of 2% vinyl carbonate (VC), 1% fluoroethylene carbonate (FEC), 0.5% vinyl sulfate (DTD) and 0.5% tris(trimethylsilyl) phosphate (TMSP).

[0010] In some embodiments, the lithium salt includes any one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiDFOB), lithium difluorooxalatophosphate (LiDFOP), lithium dioxalatoborate (LiBOB), and lithium difluorophosphate (LiPF2O2), or a combination of at least two thereof.

[0011] Some other embodiments of the present application provide a secondary battery, the secondary battery comprising: a positive electrode, a negative electrode and an electrolyte in which the positive electrode and the negative electrode are immersed, wherein the electrolyte is the above electrolyte. Some other embodiments of the present application also provide an electrical device comprising the above secondary battery.

[0012] In summary, the lone pair of electrons in the P and N atoms in the phosphorothiamidite compound molecules in the additive of the present application are protophilic and can complex the free H in the electrolyte. + , avoiding the damage of SEI caused by the increase of electrolyte acidity; at the same time, the phosphoric acid triamide compound can also oxidize and decompose on the surface of the positive electrode to form a dense inorganic layer rich in N and P, effectively reducing the impedance of SEI. The two action mechanisms of the phosphoric acid triamide compound can inhibit the continuous decomposition of the electrolyte, improve battery storage and cycle gas production, and enhance the safety performance of the battery. DETAILED DESCRIPTION

[0013] In the development of batteries, the development of electrolytes is crucial. Additives including phosphorus triamide compounds are introduced into the electrolyte. The lone pair electrons in the P and N atoms in the phosphorus triamide compound can complex the free H in the electrolyte. + , inhibit the increase of electrolyte acidity and improve the battery's cycle and storage performance.

[0014] Specifically, some embodiments of the present application provide an electrolyte, including a non-aqueous solvent, a lithium salt and an additive, wherein the additive includes a phosphorothioate compound, and the structural formula of the phosphorothioate compound is shown in the following formula (I):

[0015]

[0016] Wherein, R1-R6 are each one or more of an alkyl group, a fluoroalkyl group, and an olefin group having 1 to 3 carbon atoms, and optionally, R1-R6 are independently selected from one or more of a methyl group, an ethyl group, a difluoromethyl group, and a vinyl group. In an embodiment, the lone pair of electrons in the P and N atoms in the above-mentioned phosphorothiamidite compound molecule is protophilic and can complex the free H in the electrolyte. + , avoiding the damage of SEI caused by the increase of electrolyte acidity; at the same time, the phosphoric acid triamide compound can also oxidize and decompose on the surface of the positive electrode to form a dense inorganic layer rich in N and P, effectively reducing the impedance of SEI. The two action mechanisms of the phosphoric acid triamide compound can inhibit the continuous decomposition of the electrolyte, improve battery storage and cycle gas production, and enhance the safety performance of the battery.

[0017] In some embodiments, based on the total mass of the electrolyte, the mass proportion of the phosphoryl triamide compound is 0.1%-1.0%, and can be 0.5%. The inventors of the present application have found in their research that the amount of phosphoryl triamide compound used in the electrolyte of a lithium-ion battery is closely related to the BOL DCR (begin of life, direct-current resistance) and cyclic gas production of the battery. When the amount of phosphoryl triamide compound used is low, the free H in the electrolyte is +The complexing ability is insufficient, and more gas is produced in the later stage of the cycle, resulting in a sudden drop in the cycle; when the amount of the phosphoramide compound used is high, the BOL DCR of the battery is large, and lithium deposition of the negative electrode is likely to occur in the later stage of the cycle, affecting the cycle performance of the battery. Therefore, the amount of the phosphoramide compound added to the electrolyte needs to be limited to a reasonable range. In this embodiment, the amount of the phosphoramide compound added is 0.1%-1.0%, specifically 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, etc.

[0018] In addition, in some embodiments, based on the total mass of the electrolyte, the total mass of the additives accounts for ≥2%. The total mass of the additives in the electrolyte of the present application should be controlled to be above 2%. When the total mass of the additives accounts for ≥2%, the cycle and gas production performance of the battery are significantly improved, and when the total mass of the additives accounts for <2%, the cycle and gas production performance of the battery are improved, but the effect is limited. This is because when the total mass of the additives accounts for a low proportion, it is not enough to affect the cycle performance of the battery, so that its improvement effect is limited.

[0019] In some embodiments, the additives of the present application also include one or more of vinylene carbonate (VC), 1,3-propane sultone (PS), fluoroethylene carbonate (FEC), diethylene sulfate (DTD), methylene disulfonate (MMDS), tris(trimethylsilyl) phosphate (TMSP), and tetravinyl silane (TVSI) (which can be used as film-forming additives), and based on the total mass of the electrolyte, the mass proportion of the above additives other than the phosphorothioic acid triamide compound is 0.5%-5%.

[0020] Specifically, in some embodiments, the electrolytes can be used in combination according to actual needs.

[0021] For example, the phosphoramidite compound is a combination of one or more of vinylene carbonate (VC), 1,3-propane sultone (PS), fluoroethylene carbonate (FEC), vinyl sulfate (DTD), methylene disulfonate (MMDS), tris(trimethylsilyl) phosphate (TMSP), tetravinylsilane (TVSI), etc. In some specific embodiments, based on the total mass of the electrolyte, 2% of vinylene carbonate (VC), 1% of fluoroethylene carbonate (FEC), 0.5% of vinyl sulfate (DTD) and 0.5% of tris(trimethylsilyl) phosphate (TMSP) can be combined.

[0022] In some embodiments, the non-aqueous solvent includes a cyclic carbonate (excluding fluoroethylene carbonate (FEC)), a chain carbonate and a carboxylate, and the combination of the non-aqueous solvent can take advantage of each other and improve the comprehensive performance of the electrolyte. In some embodiments, the cyclic carbonate includes one or two of ethylene carbonate (EC) and propylene carbonate (PC), for example, the cyclic carbonate can be ethylene carbonate or propylene carbonate, or ethylene carbonate and propylene carbonate mixed in any proportion. Chain carbonates include one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC), that is, the chain carbonate can be any one of the above-listed substances, for example, the chain carbonate can be dimethyl carbonate, or diethyl carbonate, or ethyl methyl carbonate; it can also be a composition of any two or three of the above-listed substances mixed in any proportion, such as a composition of dimethyl carbonate and diethyl carbonate, or a composition of dimethyl carbonate and ethyl methyl carbonate, or a composition of diethyl carbonate and ethyl methyl carbonate. It should be noted that when the linear carbonate is a composition, there is no restriction on the ratio of the components in the composition, and the components can be mixed in any ratio.

[0023] In some embodiments, the lithium salt includes any one of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4), lithium difluorooxalate borate (LiDFOB), lithium difluorooxalate phosphate (LiDFOP), lithium dioxalate borate (LiBOB), and lithium difluorophosphate (LiPF2O2), or a combination of at least two of them. Optionally, the lithium salt is selected from lithium hexafluorophosphate with good comprehensive performance, or lithium hexafluorophosphate is used as the main material, and other lithium salts are added in appropriate amounts, and the advantages of other corresponding lithium salts are combined to improve the electrolyte performance.

[0024] The electrolyte provided in the present application for use in lithium-ion batteries can be prepared according to conventional preparation methods in the art. For example, a non-aqueous solvent is prepared in a glove box with an argon atmosphere having a water and oxygen content of less than 1 ppm in a certain proportion, and a fully dried lithium salt is dissolved in the non-aqueous solvent. An additive is added and mixed evenly to obtain an electrolyte.

[0025] Some other embodiments of the present application provide a secondary battery, which includes: a positive electrode, a negative electrode and an electrolyte in which the positive electrode and the negative electrode are immersed, wherein the electrolyte is the above-mentioned electrolyte. Some other embodiments of the present application also provide an electrical device including the above-mentioned secondary battery. Specifically, the secondary battery provided by the present application includes a shell, a positive electrode, a negative electrode, a diaphragm and the above-mentioned electrolyte, the positive electrode, the negative electrode and the diaphragm are arranged in the shell, the diaphragm is arranged between the positive electrode sheet and the negative electrode sheet, and the positive electrode, the negative electrode and the diaphragm are at least partially immersed in the electrolyte. The present invention does not limit the type and shape of the secondary battery, and the secondary battery can be a soft-pack battery, a cylindrical battery, a square shell battery, etc. In this embodiment, for example, a soft-pack secondary battery is used as an example for explanation.

[0026] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode active material loaded on at least one side of the positive electrode current collector. Among them, the positive electrode current collector can be made of foil with good conductivity and mechanical strength, such as aluminum, nickel, titanium, gold, silver, chromium, molybdenum, copper, stainless steel or carbon. In addition to foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. The positive electrode active material is arranged on any one or both sides of the two surfaces of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductive agent.

[0027] The positive electrode active material can be selected from positive electrode active materials with a layered structure, including lithium cobalt oxide (LCO), nickel cobalt manganese lithium oxide (NCM), nickel cobalt aluminum lithium oxide (NCA), etc.; it can also be selected from positive electrode active materials with an olivine structure, including lithium iron phosphate (LFP), lithium manganese iron phosphate (LMFP), etc.; it can also be selected from positive electrode active materials with a spinel structure, including lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium-rich manganese-based (LRM), etc., or a combination of any two or more of the above positive electrodes.

[0028] The positive electrode binder can be selected from one or more combinations of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), etc.

[0029] The positive electrode conductive agent can be selected from one of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, porous carbon, etc., or a combination of two or more of them mixed in any proportion.

[0030] In some embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active material loaded on at least one side of the negative electrode current collector. The negative electrode current collector can be made of a foil with good conductivity and mechanical strength, such as nickel, titanium, gold, silver, chromium, molybdenum, copper, stainless steel or carbon. In addition to foil, the negative electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. The negative electrode active material is arranged on any one or both sides of the two surfaces of the negative electrode current collector. The negative electrode active material layer includes a negative electrode active material, a negative electrode binder, an emulsifier and a negative electrode conductive agent.

[0031] The negative electrode active material can be selected from graphite or silicon-containing composite materials, including natural graphite, artificial graphite, graphite / silicon-oxygen composite materials, graphite / silicon-carbon composite materials, graphite / elemental silicon composite materials, and the like.

[0032] The negative electrode binder may be selected from any one of polyacrylic acid (PAA), sodium polyacrylate (PAAS), styrene-butadiene rubber (SBR), or a combination of two or more thereof mixed in any proportion.

[0033] Emulsifier is carboxymethyl cellulose (CMC)

[0034] The negative electrode conductive agent may be selected from one of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, porous carbon, etc., or a combination of two or more thereof mixed in any proportion.

[0035] In some embodiments, the separator can be selected from a polyethylene porous film (PE), a polypropylene porous film (PP), and a polyethylene / polypropylene composite porous film (PE / PP / PE).

[0036] The secondary battery is prepared as follows:

[0037] Positive electrode preparation: The positive electrode active material, positive electrode conductive agent and positive electrode binder are mixed and dispersed in a solvent to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector, dried at room temperature and then transferred to an oven for vacuum drying. The dried positive electrode is cold-pressed to obtain a positive electrode sheet. The ratio between the components in the positive electrode can be set with reference to the conventional ratio and is not limited here.

[0038] Negative electrode preparation: The negative electrode active material, negative electrode conductive agent, negative electrode binder and emulsifier are mixed and dispersed in deionized water to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector, dried at room temperature and then transferred to an oven for vacuum drying. The dried negative electrode is cold pressed to obtain a negative electrode sheet. The ratio between the components in the negative electrode can be set with reference to the conventional ratio and is not limited here.

[0039] Battery assembly: stack the negative electrode, separator, and positive electrode in order, with the separator between the positive and negative electrodes to isolate them. Put the stacked bare cells into aluminum-plastic film to obtain dry cells, which are vacuum dried at 100°C to remove water. Inject the prepared electrolyte into the dry cells and seal them, and perform electrolyte formation to obtain soft-pack secondary batteries.

[0040] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the examples are all commercially available.

[0041] Example 1

[0042] (1) Preparation of electrolyte

[0043] In a glove box filled with argon atmosphere, ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a mass ratio of 3:6:1 to obtain a non-aqueous solvent; dried lithium hexafluorophosphate (LiPF6) and lithium bis(fluorosulfonyl)imide (LiFSI) are added to the non-aqueous solvent and mixed evenly, and then a phosphorothioate compound of hexaethylphosphorothioate (wherein R1-R6 are ethyl groups) is added, and the structural formula thereof is as follows:

[0044]

[0045] After that, vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl sulfate (DTD), and tris(trimethylsilyl) phosphate (TMSP) were added to obtain an electrolyte. Among them, the concentration of LiPF6 in the electrolyte is 0.7 mol / L, the concentration of LiFSI in the electrolyte is 0.4 mol / L, and based on the total mass of the electrolyte, the mass percentage of the additive hexaethylphosphoric triamide is 0.1%, the mass percentage of vinylene carbonate (VC) is 2%, the mass percentage of fluoroethylene carbonate (FEC) is 1%, the mass percentage of vinyl sulfate (DTD) is 0.5%, and the mass percentage of tris(trimethylsilyl) phosphate (TMSP) is 0.5%.

[0046] (2) Preparation of positive electrode:

[0047] The positive electrode active material lithium manganese iron phosphate, polyvinylidene fluoride as a binder and SuperP as a conductive agent are mixed in a weight ratio of 98:1:1, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the system becomes uniform and transparent to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil. After that, the aluminum foil is dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain the positive electrode.

[0048] (3) Preparation of negative electrode:

[0049] Artificial graphite is used as the negative electrode active material, Super P is used as the conductive agent, sodium carboxymethyl cellulose (CMC-Na) is used as the thickener, and styrene-butadiene rubber (SBR) is used as the binder. They are mixed in a mass ratio of 96:1:1:2, and deionized water is added. The negative electrode slurry is obtained under the action of a vacuum mixer. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil. After that, the copper foil is dried at room temperature and transferred to an oven for drying, and then the negative electrode is obtained by cold pressing and slitting.

[0050] (4) Preparation of diaphragm:

[0051] A 12 μm thick polyethylene was selected as the separator.

[0052] (5) Preparation of secondary batteries:

[0053] The negative electrode, separator, and positive electrode prepared above are stacked in order, and the separator is between the positive and negative electrodes to isolate the positive and negative electrodes. The stacked bare cells are placed in an aluminum-plastic film to obtain dry cells, which are vacuum dried at 100°C to remove water. The prepared electrolyte is injected into the dry cells and sealed, and the electrolyte is formed to obtain a soft-pack secondary battery.

[0054] Example 2

[0055] The preparation method is consistent with that of Example 1, except that in Example 2, based on the total mass of the electrolyte, the mass percentage of hexaethylphosphoramidite is 0.3%.

[0056] Example 3

[0057] The preparation method is consistent with that of Example 1, except that in Example 3, based on the total mass of the electrolyte, the mass percentage of hexaethylphosphoramidite is 0.5%.

[0058] Example 4

[0059] The preparation method is consistent with that of Example 1, except that in Example 3, based on the total mass of the electrolyte, the mass percentage of hexaethylphosphoramidite is 1.0%.

[0060] Example 5

[0061] The preparation method is consistent with that of Example 1, except that in Example 5, the phosphorothioic acid triamide compound is hexamethylphosphorothioic acid triamide, and its structural formula is as follows:

[0062]

[0063] Example 6

[0064] The preparation method is consistent with that of Example 1, except that in Example 6, the phosphorothiamidite compound is hexa(difluoromethyl)phosphothiamidite, and its structural formula is as follows:

[0065]

[0066] Example 7

[0067] The preparation method is consistent with that of Example 1, except that in Example 7, the phosphorothioic acid triamide compound is hexavinyl phosphorothioic acid triamide, and its structural formula is as follows:

[0068]

[0069] Example 8

[0070] The preparation method is consistent with that of Example 1, except that in Example 8, based on the total mass of the electrolyte, the mass percentage of hexaethylphosphoramidite is 0.5%, and vinylene carbonate (VC), fluoroethylene carbonate (FEC), diethylene sulfate (DTD), and tris(trimethylsilyl) phosphate (TMSP) are not used.

[0071] Example 9

[0072] The preparation method is consistent with that of Example 1, except that in Example 9, based on the total mass of the electrolyte, the mass percentage of hexaethylphosphoric triamide is 0.5%, the mass percentage of vinylene carbonate (VC) is 0.2%, the mass percentage of vinyl sulfate (DTD) is 0.15%, and the mass percentage of tris(trimethylsilyl) phosphate (TMSP) is 0.15%.

[0073] Example 10

[0074] The preparation method is consistent with that of Example 1, except that in Example 9, based on the total mass of the electrolyte, the mass percentage of hexaethylphosphoric triamide is 0.5%, the mass percentage of vinylene carbonate (VC) is 2%, the mass fraction of fluoroethylene carbonate (FEC) is 1%, the mass percentage of vinyl sulfate (DTD) is 1%, and the mass percentage of tris(trimethylsilyl) phosphate (TMSP) is 1%.

[0075] Comparative Example 1

[0076] The preparation method is consistent with that in Example 1, except that in Comparative Example 1, based on the total mass of the electrolyte, the mass percentage of hexaethylphosphoramidite is 0%.

[0077] Comparative Example 2

[0078] The preparation method is consistent with that in Example 1, except that in Comparative Example 2, based on the total mass of the electrolyte, the mass percentage of hexaethylphosphoramidite is 0.01%.

[0079] Comparative Example 3

[0080] The preparation method is consistent with that in Example 1, except that in Comparative Example 3, based on the total mass of the electrolyte, the mass percentage of hexaethylphosphoramidite is 1.5%.

[0081] The secondary batteries in the above-mentioned Examples 1-10 and Comparative Examples 1-3 can be subjected to the following performance tests by the following methods:

[0082] The electrolytes prepared in Examples 1-10 and Comparative Examples 1-5 were respectively assembled with a graphite negative electrode, a lithium iron manganese phosphate positive electrode and a polyethylene separator into graphite-lithium iron manganese phosphate full batteries, and the cycle and gas production performance of the assembled graphite-lithium iron manganese phosphate full batteries were tested.

[0083] Cycle performance: The graphite-lithium manganese iron phosphate full batteries after capacity division were placed in a constant temperature box at 45°C, and the charge and discharge cycles were carried out at a charge and discharge rate of 1C in the voltage range of 2.8V-4.2V. The discharge capacity of each cycle was recorded. When the battery capacity reached 80% of the first cycle capacity, the test was stopped and the number of cycles of each battery was counted.

[0084] Storage performance: The graphite-manganese iron phosphate lithium full batteries after capacity division were charged to 4.2V at a constant current and constant voltage rate of 0.33C, with a cut-off current of 0.05C, and the initial volume of each graphite-manganese iron phosphate lithium full battery was recorded. The fully charged graphite-manganese iron phosphate lithium full batteries were then stored in a constant temperature box at 60°C, and the volume test was performed every 7 days. After the volume was measured after 56 days of storage, the test was terminated. The results are shown in Table 1 below:

[0085] Table 1. Secondary battery performance test results in Examples 1-10 and Comparative Examples 1-3

[0086]

[0087]

[0088] From the comparison between Examples 1-10 and Comparative Example 1, it can be seen that the present application introduces an additive including a phosphoryl triamide compound into the electrolyte, and the structural formula of the phosphoryl triamide compound is shown in the following formula (I):

[0089] Wherein, R1-R6 are each one or more of an alkyl group, a fluoroalkyl group, and an olefin group having 1 to 3 carbon atoms, so that the high temperature cycle and gas generation performance of the graphite-manganese iron phosphate lithium battery can be significantly improved, indicating that the phosphorothioic acid triamide compound in the additive of the present application can eliminate free H in the electrolyte. + , protecting SEI from being destroyed, thereby improving the cycle and storage performance of the battery. Specifically, the lone pair of electrons in the P and N atoms in the above-mentioned phosphoryl triamide compound molecules are protonic and can complex the free H + , avoiding the damage of SEI caused by the increase of electrolyte acidity; at the same time, the phosphoric acid triamide compound can also oxidize and decompose on the surface of the positive electrode to form a dense inorganic layer rich in N and P, effectively reducing the impedance of SEI. The two action mechanisms of the phosphoric acid triamide compound can inhibit the continuous decomposition of the electrolyte, improve battery storage and cycle gas production, and enhance the safety performance of the battery.

[0090] Further, from the comparison between Examples 1-4 and Comparative Examples 1-3, it can be seen that an appropriate amount of phosphoryl triamide compound needs to be introduced into the electrolyte, that is, based on the total mass of the electrolyte, the mass proportion of the additive is 0.1%-1.0%, and can be 0.5%. This is because when the amount of phosphoryl triamide compound used is low, the free H in the electrolyte is + The complexing ability is insufficient, and more gas is produced in the later stage of the cycle, resulting in a sudden drop in the cycle; when the amount of the phosphorus amide compound used is high, the DCR of the battery is large, and lithium deposition and gas production are likely to occur at the negative electrode in the later stage of the cycle, affecting the cycle performance of the battery. Therefore, the amount of the phosphorus amide compound added to the electrolyte needs to be limited to a reasonable range. In this embodiment, based on the total mass of the electrolyte, the amount of the phosphorus amide compound added is 0.1%-1.0%, and preferably 0.5%, because when the mass proportion of the phosphorus amide compound is 0.5%, it can better complex the free H in the electrolyte. + At the same time, the DCR of the battery is not significantly increased, thus not affecting the cycle performance of the battery.

[0091] From the comparison between Example 3 and Examples 8-10, it can be seen that based on the total mass of the electrolyte, the total mass proportion of the additives in the electrolyte of the present application should be controlled at more than 2%. When the total mass proportion of the additives is ≥2%, the cycle and gas production performance of the battery are significantly improved, and when the total mass proportion of the additives is <2%, the cycle and gas production performance of the battery are improved, but the improvement effect is limited. This is because when the total mass proportion of the additives is low, it is not enough to affect the cycle performance of the battery, so that its improvement effect is limited. In addition, based on the total mass of the electrolyte, the mass proportion of additives other than phosphorothioate compounds (such as film-forming additives) in the additives is 0.5%-5%. Within this range, the cycle performance of the corresponding battery can be effectively improved without affecting the performance of the additives.

[0092] The features of several embodiments are summarized above so that those skilled in the art can better understand aspects of the present invention. Those skilled in the art should understand that they can easily use the present invention as a basis to design or modify other processes and structures for implementing the same purpose and / or achieving the same advantages as the embodiments introduced herein. Those skilled in the art should also appreciate that this equivalent construction does not deviate from the spirit and scope of the present invention, and that they can make multiple changes, substitutions and changes herein without departing from the spirit and scope of the present invention.

Claims

1. An electrolyte, characterized in that: The invention comprises a non-aqueous solvent, a lithium salt and an additive, wherein the additive comprises a phosphorothiadiamide compound, and the structural formula of the phosphorothiadiamide compound is shown in the following formula (I): Wherein, R1-R6 are each one or more of an alkyl group, a fluoroalkyl group, and an olefin group having 1 to 3 carbon atoms.

2. The electrolyte according to claim 1, characterized in that R1-R6 are independently selected from one or more of methyl, ethyl, difluoromethyl and vinyl.

3. The electrolyte according to claim 1, characterized in that Based on the total mass of the electrolyte, the mass proportion of the phosphorothiamide compound is 0.1%-1.0%.

4. The electrolyte according to claim 3, characterized in that Based on the total mass of the electrolyte, the mass proportion of the phosphorothiamide compound is 0.5%.

5. The electrolyte according to claim 1, characterized in that Based on the total mass of the electrolyte, the mass proportion of the additive is ≥2%.

6. The electrolyte according to claim 3, characterized in that The additives also include one or more of vinylene carbonate (VC), 1,3-propane sultone (PS), fluoroethylene carbonate (FEC), diethylene sulfate (DTD), methylene methanedisulfonate (MMDS), tris(trimethylsilyl) phosphate (TMSP), and tetravinylsilane (TVSI).

7. The electrolyte according to claim 6, characterized in that The additives also include vinylene carbonate (VC), diethyl sulfate (DTD) and tris(trimethylsilyl)phosphate (TMSP).

8. The electrolyte according to claim 1, characterized in that The lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiDFOB), lithium difluorooxalatophosphate (LiDFOP), lithium dioxalatoborate (LiBOB), and lithium difluorophosphate (LiPF2O2).

9. A secondary battery, characterized in that: include: A positive electrode, a negative electrode and an electrolyte in which the positive electrode and the negative electrode are immersed, wherein the electrolyte is the electrolyte according to any one of claims 1-8.

10. An electrical device, characterized in that: The secondary battery according to claim 9 is included.

Citation Information

Patent Citations

  • Electrolyte, electrochemical device and electronic device

    CN113424353A

  • Silicon-based energy storage devices with phosphorus containing electrolyte additives

    US20200144672A1